GOOD CORPORATE GOVERNANCE DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI DAN KINERJA PERUSAHAAN (Studi Empiris Perusahaan Terindeks Saham LQ45 di Bursa Efek Indonesia Periode 2021-2024) - Iffah Nur Shadrina; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2026)
This study aims to analyze the effect of Good Corporate Governance (GCG) and Corporate Social Responsibility (CSR) on the value and performance of companies indexed by LQ45 shares on the Indonesia Stock Exchange (IDX) during the 2021-2024 period. The problem examined is whether GCG components—consisting of Managerial Ownership (MO), Institutional Ownership (IO), Proportion of Independent Commissioners (IC), Audit Committee (AC), and Board of Director Size (BOD)—along with CSR, influence company value (PBV) and performance (ROE). This research adapts the study by Asyik et al. (2024). Using multiple linear regression with sustainability reports and Bloomberg financial data, and a sample of 17 companies that consistently applied GCG and disclosed CSR during 2021-2024, the results show that IO and IC positively influence both firm value and performance, while AC negatively influences both. BOD positively affects firm performance only. MO and CSR show no significant effect on either firm value or performance. These findings indicate that GCG quality and quantity aspects have not been fully prioritized and CSR disclosure has not become a primary consideration for investors in Indonesia during 2021-2024.